Binding of MBNL1 to CUG repeats slows 5'-to-3' RNA decay by XRN2 in a cell culture model of type I myotonic dystrophy - Zhang, Junzhen, author; Wilusz, Carol J., advisor; Wilusz, Jeffrey, advisor; Duval, Dawn, committee member; Di Pietro, Santiago, committee member; Yao, Tingting, committee member (Colorado State University. Libraries, 2017)
Type I myotonic dystrophy (DM1) is a multi-systemic inherited disease caused by expanded CTG repeats within the 3' UTR of the dystrophia myotonica protein kinase (DMPK) gene. The encoded CUG repeat-containing mRNAs are toxic to the cell and accumulate in nuclear foci, where they sequester cellular RNA-binding proteins such as the splicing factor Muscleblind-1 (MBNL1). This leads to widespread changes in gene expression. Currently, there is no treatment or cure for this disease. Targeting CUG repeat-containing mRNAs for degradation is a promising therapeutic avenue for myotonic dystrophy, but we know little about how and where these mutant mRNAs are naturally decayed. We established an inducible C2C12 mouse myoblast model to study decay of reporter mRNAs containing the DMPK 3' UTR with 0 (CUG0) or ~700 (CUG700) CUG repeats and showed that the CUG700 cell line exhibits characteristic accumulation of repeat-containing mRNA in nuclear foci. We utilized qRT-PCR and northern blotting to assess the pathway and rate of decay of these reporter mRNAs following depletion of mRNA decay factors by RNA interference. We have identified four factors that influence decay of the repeat-containing mRNA – the predominantly nuclear 5' 3' exonuclease XRN2, the nuclear exosome containing RRP6, the RNA-binding protein MBNL1, and the nonsense-mediated decay factor, UPF1. We have discovered that the 5' end of the repeat-containing transcript is primarily degraded in the nucleus by XRN2, while the 3' end is decayed by the nuclear exosome. Interestingly, we have shown for the first time that the ribonucleoprotein complex formed by the CUG repeats and MBNL1 proteins represents a barrier for XRN2-mediated decay. We suggest that this limitation in XRN2-mediated decay and the resulting delay in degradation of the repeats and 3' region may play a role in DM1 pathogenesis. Additionally, our results support previous studies suggesting that UPF1 plays a role in initiating the degradation of mutant DMPK transcripts. This work uncovers a new role for MBNL1 in DM1 and other CUG-repeat expansion diseases and identifies the nuclear enzymes involved in decay of the mutant DMPK mRNA. Our model has numerous applications for further dissecting the pathways and factors involved in removing toxic CUG-repeat mRNAs, as well as in identifying and optimizing therapeutics that enhance their turnover.
Keywords: DMPK; RNA decay; XRN2; MBNL1; C2C12 mouse myoblasts; type I myotonic dystrophy